Predictive performance of the variation rate of the driving pressure on the outcome of invasive mechanical ventilation in patients with acute respiratory distress syndrome - Jing, Hui-Dan; Tian, Jun-Ying; Li, Wei; He, Bing-Ling; Li, Hong-Chao; Jian, Fu-Xia; Shang, Cui; Shen, Feng (Chinese journal of traumatology, 2024)
To assess the value of the driving pressure variation rate (ΔP%) in predicting the outcome of weaning from invasive mechanical ventilation in patients with acute respiratory distress syndrome. In this case-control study, a total of 35 patients with moderate-severe acute respiratory distress syndrome were admitted to the intensive care unit between January 2022 and December 2022 and received invasive mechanical ventilation for at least 48 h were enrolled. Patients were divided into successful weaning group and failed weaning group depending on whether they could be removed from ventilator support within 14 days. Outcome measures including driving pressure, PaO2:FiO2, and positive end-expiratory pressure, etc. were assessed every 24 h from day 0 to day 14 until successful weaning was achieved. The measurement data of non-normal distribution were presented as median (Q1, Q3), and the differences between groups were compared by Wilcoxon rank sum test. And categorical data use the Chi-square test or Fisher's exact test to compare. The predictive value of ΔP% in predicting the outcome of weaning from the ventilator was analyzed using receiver operating characteristic curves. Of the total 35 patients included in the study, 17 were successful vs. 18 failed in weaning from a ventilator after 14 days of mechanical ventilation. The cut-off values of the median ΔP% measured by Operator 1 vs. Operator 2 in the first 4 days were ≥ 4.17% and 4.55%, respectively (p < 0.001), with the area under curve of 0.804 (sensitivity of 88.2%, specificity of 64.7%) and 0.770 (sensitivity of 88.2%, specificity of 64.7%), respectively. There was a significant difference in mechanical ventilation duration between the successful weaning group and the failure weaning group (8 (6, 13) vs. 12 (7.5, 17.3), p = 0.043). The incidence of ventilator-associated pneumonia in the successful weaning group was significantly lower than in the failed weaning group (0.2‰ vs. 2.3‰, p = 0.001). There was a significant difference noted between these 2 groups in the 28-day mortality (11.8% vs. 66.7%, p = 0.003). The median ΔP% in the first 4 days of mechanical ventilation showed good predictive performance in predicting the outcome of weaning from mechanical ventilation within 14 days. Further study is needed to confirm this finding.